Analisis SWOT Model Bisnis Kanvas dalam Strategi Peningkatan Persaingan Rumah Sakit - Rahayu, Tri Wachyuni; Rahim, Agus Hadian; Sri Suwarsi; Muhardi; Ahmad Arif Nurrahman (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Increasing demand from the public to obtain excellent and quality health services and the increasing growth of hospitals, both private and government, will lead to business competition between hospitals. This study aims to obtain a Business Strategy Plan as a result of the SWOT Analysis Business Model Canvas the Ciamis District Hospital in order to increase hospital business competition. The type of research is Mix Method approach Concurrent Triangulation Design. Using quantitative and qualitative data analysis. The survey results based on the patient's perspective stated that the service quality of the Ciamis District Hospital was in the good category. The results of the calculation of the IE Matrix in cell II position, the strategy used is Grow and Build. From the results of the SWOT Business Model Canvas is in quadrant 1, with aggressive, then using the SO (Strength Opportunity) Strategy. Thus, the Ciamis District Hospital can formulate strategies in the form of market development, market penetration, product development and integration, through several programs, namely capacity building for apparatus resources, development/standardization of resources and health financing, procurement, improvement of hospital infrastructure and capacity building resources health human resources. Abstrak. Semakin tingginya permintaan masyarakat untuk memperoleh pelayanan kesehatan yang prima dan berkualitas dan meningkatnya pertumbuhan rumah sakit, baik swasta maupun pemerintah akan menimbulkan persaingan bisnis antar rumah sakit. Penelitian ini bertujuan untuk memperoleh Rencana Strategi Bisnis hasil Analisis SWOT Model Bisnis Kanvas RSUD Kabupaten Ciamis dalam upaya peningkatan persaingan bisnis rumah sakit. Jenis penelitian adalah Mix Method dengan pendekatan Concurrent Triangulation Design. Menggunakan analisis data kuantitatif dan kualitatif. Hasil survei berdasarkan perspektif pasien menyatakan kualitas pelayanan RSUD kabupaten Ciamis termasuk kategori Baik. Hasil perhitungan Matriks IE pada posisi sel II, strategi yang dilakukan adalah Grow and Build. Dari hasil skoring SWOT Model Bisnis Kanvas berada pada kuadran 1, dengan kriteria aggresive, sehingga menggunakan Strategi SO (Strength Opportunity). Dengan demikian RSUD Kabupaten Ciamis dapat merumuskan strategi berupa pengembangan pasar, penetrasi pasar, pengembangan produk dan integratif melalui beberapa program yaitu peningkatan kapasitas sumber daya aparatur, pengembangan/standarisasi sumber daya dan pembiayaan kesehatan, pengadaan, peningkatan sarana prasarana rumah rakit dan peningkatan kapasitas sumber daya manusia kesehatan.